Screening and Identification of Cellulolytic Bacteria from Public Cemetery Soil - Siti Nur Syarifah; Triastuti Rahayu; Erma Musbita Tyastuti; Yasir Sidiq (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: A public cemetery (TPU) is where bodies are buried. Before being buried, the body is wrapped in a shroud or full clothes and sometimes put in a coffin. These materials contain cellulose, a substrate for cellulolytic microorganisms, including bacteria, to decompose. Exploration of cellulolytic bacteria in TPU has not been found, even though TPU holds potential cellulolytic bodies. This study aims to determine the cellulolytic potential and identify bacterial isolates from TPU. Methods: 36 bacterial isolates tested for cellulolytic potential have been isolated from TPU Pracimaloyo Kartasura, Sukoharjo. Selection of cellulolytic bacteria used selective Carboxymethyl Cellulose (CMC) media dripped with Congo red 0.1%, while identification was based on colony morphology and Gram staining. Results: This study obtained one isolate (2.78%) showing high cellulolytic activity with a cellulolytic index (IS) 7, namely P14, 24 isolates (66.67%) in the